2019
DOI: 10.1016/j.physe.2019.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Phase filters for a novel kind of asymmetric transport – Scientific prospects and opportunities for possible applications

Abstract: We present the concept of nonreciprocal interferometers. These two-way devices let particles pass in both directions, but in one direction break the phase of the particles' wave functions. Such filters can be realized by using, for example, asymmetric quantum rings. Furthermore, we propose arrangements of these interferometers to obtain larger interferometers which are expected to exhibit a puzzling behavior that resembles Maxwell demon action. We indicate an opportunity to resolve this puzzle experimentally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The longer Wigner time delay leads to a higher probability for inelastic interaction with defects localized in the scattering region and therefore affects the conductivity. Thus, in such cases, non-reciprocal Wigner time delays may lead to non-reciprocal two-terminal conductance 5,9,16 . Analyzing the properties of buckled silicene AB rings, Szafran et al have shown that inter-valley scattering converts oscillations of the Wigner time delay into conductance oscillations 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The longer Wigner time delay leads to a higher probability for inelastic interaction with defects localized in the scattering region and therefore affects the conductivity. Thus, in such cases, non-reciprocal Wigner time delays may lead to non-reciprocal two-terminal conductance 5,9,16 . Analyzing the properties of buckled silicene AB rings, Szafran et al have shown that inter-valley scattering converts oscillations of the Wigner time delay into conductance oscillations 17 .…”
Section: Discussionmentioning
confidence: 99%
“…To stay first with two-terminal electronic devices, we note that the rings can also function as devices that transport particles in one direction more as waves, and in the reverse direction as particles. They also provide for devices that transport particles phase-coherently in forward direction, and incoherently in reverse direction, or, in other words, devices that feature quantum transport in one direction, and more classical transport in the other [41]. The basic principles require neither rings nor are they specific to electrons [23].…”
Section: Unitary and Non-unitary Evolutions Combined In An Asymmetric...mentioning
confidence: 99%
“…Materials can also be artificially designed and metamaterials can be devised to have properties shaped by the non-unitary and unitary evolution of quantum states [41], see for example Figure 6. This 2D material consists of ring-shaped molecules that break inversion symmetry, where each molecule acts as an asymmetric, non-unitary quantum ring.…”
Section: Non-unitary Quantum Materialsmentioning
confidence: 99%
“…The photon reservoirs could be replaced by any incoherent source of particles or energy, e.g., resistors with Johnson-Nyquist noise. Devices closely related to the presented chiral waveguide, but being based on coherence filters, have been presented in[48,49]. A possible solid-state realization employing asymmetric quantum rings featuring inelastic scattering works similarly to our quantum-optical implementation and would pump electrons instead of photons[50,51].…”
mentioning
confidence: 99%